[Teaching a lesson ; Life in a monastery ; Dinosaurs alive [videorecording] - Lazaro, Cheche (The Probe Team, 1991)
Militant teachers go on a hunger strike to protest their removal from their jobs by Secretary Isidro Carino for leading a strike in 1990. In a Benedictine Abbey in Bukidnon, the monks lure a rigorous work and prayer life. Animated dinosaurs facscinates winners and open their minds to life million years ago.